DEVELOPMENT OF A MATHEMATICS-BASED MODULE AUGMENTED REALITY (AR) ON SPACE BUILDING MATERIAL IN CLASS V PRIMARY SCHOOL - Elkafiyani, Salsabilla Briliana; Alyani, Fitri (STKIP PGRI Tulungagung, 2025)
This research aims to develop a mathematics module on geometric mate-rial that is suitable for use as a teaching medium for mathematics subjects in class V of elementary schools and is useful as an additional reference for teachers in teaching and learning activities. The research method used is the research and development method (Research and Development). Researchers use the RnD (Research and Development) research method using the ADDIE development model in their activities and use question-naires to collect data related to practicality and tests to measure learning outcomes after reading the module. The data analysis carried out in this research was a data analysis technique using a descriptive scale. The re-search results show that the mathematics module is based on space aug-mented reality developed is feasible and practical for use in mathematics learning. The results of the validation carried out by material experts, in this study, got a score interval of